Social Inhibition and Depressive Symptoms among Couples with Children with Autism Spectrum Disorder: The Mediating Role of Perceived Family Support - Ting Pan; Tinakon Wongpakaran; Nahathai Wongpakaran; Bijing He; Danny Wedding (Medicina, 2024)
Background and Objectives: A limited understanding exists regarding the intricate dynamics between the levels of social inhibition exhibited by both wives and husbands concerning their perceived family support and depressive symptoms, particularly within couples who are parents of children diagnosed with autism spectrum disorder (ASD). Materials and Methods: This study used the actor–partner interdependence mediation model to analyze data collected from 397 pairs of Chinese parents with children diagnosed with ASD. Results: The findings of the study revealed significant indirect actor effects, indicating that the levels of social inhibition exhibited by both wives and husbands were associated with their own depressive symptoms through their respective perceptions of family support. In general, the study did not find significant partner effects, except for some indirect effects of wives on their husbands’ depressive symptoms through the wives’ perceived social support. Conclusions: In line with related studies, social inhibition was associated with depressive symptoms. At the same time, perceived family support could be a mediator of depression. Gender differences in emotional expression, influenced by cultural norms and distinct role expectations within the family context, may elucidate why only wives’ perceived family support could impact husbands’ depressive symptoms. These results underscore the potential importance of interventions aimed at addressing social inhibition and enhancing perceived family support to alleviate depressive symptoms in this population. Additionally, encouraging family support for both wives and husbands’ involvement in collaboration may be of benefit in improved outcomes for both parents and children within families affected by ASD.